The Influence of Legal Politics in the Implementation of Government Cooperation of Small-Scale Enterprises of Local Government - Cut Zulfahnur Syafitri; kurdi; Asep Sumaryana; Budiman Rusli (Dinasti Research, 2024)
The implementation of infrastructure development in the regions continues to experience obstacles despite the conception of PPP. Obstacles as contained in PPP in the regions can occur considering the cost of PPP in the regions is not as large as PPP in the central government and in connection with this, a conception of Small Scale PPP is needed that can be implemented by the Regional Government so that later development in the regions can be carried out with the PPP mechanism. The implementation of small-scale PPP in the regions is certainly inseparable from legal politics because it is legal politics that can determine the direction of policy. In connection with this, the author wants to conduct an analysis with the formulation of the problem in the form of How is the Influence of Legal Politics in the Implementation of Small-Scale Business Entity Government Cooperation of Local Governments? The results of this study are that small-scale PPP is strongly influenced by legal politics where legal politics in this case not only directs the course of infrastructure development with the PPP scheme, but also serves as a safeguard for the interests of all parties involved, including contractors, investors, and affected communities.